DEVELOPMENT OF THE DIGITAL ECOSYSTEM OF THE LABOUR MARKET (INNOVATIVE ECONOMY, 2024)
Atamaniuk R.F. DEVELOPMENT OF THE DIGITAL ECOSYSTEM OF THE LABOUR MARKETPurpose. The aim of the article is to study and analyse the key trends, impact and changes occurring in the labour market in the context of digital transformation.Methodology of research. The following research methods were used to achieve this goal: literary review – to conduct a broad review of existing scientific publications, articles, reports of well-known think tanks and organizations, which made it possible to identify the main trends and challenges associated with the development of the digital ecosystem of the labour market; statistical analysis method – to use big data; statistical analysis – to determine the quantitative indicators of employment, the structure of the labour market, changes in demand and supply for labour in various sectors of the economy; case-stud method – to analyse specific examples of companies and industries that have successfully adapted to the conditions of the digital economy, introducing innovative approaches to labour organization and talent attraction.Findings. The study showed that in the context of digital transformation, there are significant changes in the aspects of work, employment and organizational structures of work, which carry both potential threats and new perspectives. It was determined that the platform economic model in the digital age is a reflection of the integration of information, technologies and specialized fields, which affects the organization of employment, the nature of existing and future work tasks. It is determined that within the framework of the platform economy there is a transformation of the foundations of the division of labour, which is now realized through the collective use of information and technological means for the formation of ecosystems of cooperation, which makes it possible to substantiate the prospects for further development of the labour market, in particular the growth of the number of remote workers and the impact of digitalization on the change of business practices.Originality. The systematic approach to the study of the transformation of labour relations in the digital economy was improved, new forms of organization of labour and employment were determined, as well as the analysis of the influence of digital platforms on the labour market, which, unlike existing approaches, determines the peculiarities of job formation, and forms new trends in the organization of labour and employment at the global level,.Practical value. Valuable insights and recommendations were provided for various stakeholders, including politicians, business leaders, educational institutions and employees, to adapt to the rapid changes in the labour market caused by digitalization. The article highlights the importance of understanding the dynamics of the digital economy and its impact on job creation, skills requirements and forms of employment.Key words: labour market, digitalization, digital platforms, gig economy, forms of employment, platform infrastructure.
Keywords: labour market; digitalization; digital platforms; gig economy; forms of employment; platform infrastructure.